2023
DOI: 10.3390/nano13091495
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antibacterial Efficacy of Cetylpyridinium Chloride-Montmorillonite Containing PMMA Resin Cement

Abstract: Despite being able to adhesively restore teeth, adhesives and cement do not possess any anticariogenic protection potential, by which caries recurrence may still occur and reduce the clinical lifetime of adhesive restorations. Several antibacterial agents have been incorporated into dental adhesives and cement to render them anticariogenic. Due to an additional therapeutic effect, such materials are classified as ‘dental combination products’ with more strict market regulations. We incorporated cetylpyridinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Yamamoto et al (2022) conducted a similar study and found that concentrations of 5%-7.5% CPC -modified MMT (MMT-CPC) by weight could effectively prevent the formation of biofilms without affecting mechanical strength or bonding properties. The result was further supported by another study [44], concluding that dental cement containing MMT-CPC released CPC to prevent biofilm growth for up to two months. Notably, despite being stored in water for six months, antibacterial properties were still demonstrable [44].…”
Section: Cetylpyridinium Chloride (Cpc) -Montmorillonitesupporting
confidence: 52%
See 3 more Smart Citations
“…Yamamoto et al (2022) conducted a similar study and found that concentrations of 5%-7.5% CPC -modified MMT (MMT-CPC) by weight could effectively prevent the formation of biofilms without affecting mechanical strength or bonding properties. The result was further supported by another study [44], concluding that dental cement containing MMT-CPC released CPC to prevent biofilm growth for up to two months. Notably, despite being stored in water for six months, antibacterial properties were still demonstrable [44].…”
Section: Cetylpyridinium Chloride (Cpc) -Montmorillonitesupporting
confidence: 52%
“…The result was further supported by another study [44], concluding that dental cement containing MMT-CPC released CPC to prevent biofilm growth for up to two months. Notably, despite being stored in water for six months, antibacterial properties were still demonstrable [44]. In another study, Otsubo et al demonstrated MMTs ability to incorporate CPC, and its capacity to deliver CPC in composites formulated with resins for orthodontic applications [91].…”
Section: Cetylpyridinium Chloride (Cpc) -Montmorillonitesupporting
confidence: 52%
See 2 more Smart Citations
“…Conjugating the non-biodegradable polymer poly(methyl methacrylate) (PMMA) with antimicrobial agents has been established as a treatment for periprosthetic joint infection [ 86 ]. Several antibacterial agents have been incorporated into dental adhesives and cement to render them anticariogenic [ 87 ]. Conversely, research on imparting antibacterial properties to the biodegradable polymer PLGA/β-TCP composite is still in the development stage [ 88 ].…”
Section: Nanogel and Regenerative Medicinementioning
confidence: 99%